Salt-coated infrared nonlinear optical crystal as well as preparation method and application thereof

By using [Ba22(SO4)5][Zn14Ga18S58] material and using high-temperature solid-state method to prepare infrared nonlinear optical crystals, the problem of difficult balance between laser damage threshold and second-order frequency multiplication coefficient of existing materials has been solved, and achieved Efficient infrared nonlinear optical performance.

CN119332345AActive Publication Date: 2025-01-21FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310895828.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-21
Estimated Expiration
2043-07-20

AI Technical Summary

Technical Problem

The existing infrared nonlinear optical crystal materials are difficult to balance between laser damage threshold and second-order frequency multiplication coefficient, which limits their application prospects.

Method used

A salt-coated infrared nonlinear optical crystal material with the chemical formula [Ba22(SO4)5][Zn14Ga18S58] is used to prepare the material through a high-temperature solid-state method to achieve its excellent second-order nonlinear optical properties and high laser damage threshold.

Benefits of technology

The powder frequency doubling strength of this material reaches 1.0 to 2.0 times that of the commercial material AgGaS2, and the laser damage threshold is 30 to 40 times that of the AgGaS2 crystal, effectively achieving a balance between a large second-order frequency doubling coefficient and a high laser damage threshold.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332345A_ABST
    Figure CN119332345A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of inorganic nonlinear optical materials, and particularly discloses a salt-coated infrared nonlinear optical crystal as well as a preparation method and application thereof. The molecular formula of the optical crystal is [Ba22 (SO4) 5] [Zn14Ga18S58], the crystal structure belongs to a cubic system, the space group is # imgabs0, the optical crystal has excellent second-order nonlinear optical properties, phase matching, a wide light transmission range and strong infrared frequency doubling response can be achieved in an infrared band, the powder frequency doubling strength of the optical crystal can reach 1.0-2.0 times of that of a commercial material AgGaS2, and the optical crystal has a wide application prospect. The laser damage threshold of the AgGaS2 crystal is 30-40 times that of the AgGaS2 crystal, and the AgGaS2 crystal has important application value in the high-tech fields of laser frequency conversion, near-infrared probes, photorefractive information processing and the like, and is particularly used for infrared detectors and infrared lasers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic nonlinear optical materials, and in particular relates to a salt-coated infrared nonlinear optical crystal, and a preparation method and application thereof. Background Art

[0002] Nonlinear optical crystals are a very important type of optoelectronic functional materials, which are widely used in laser communications, optical information processing, integrated circuits and military technology. Generally speaking, an ideal nonlinear optical crystal must meet the following conditions: (1) a large second-order harmonic frequency coefficient; (2) a high laser damage threshold; (3) a moderate birefringence; (4) a wide optical transmission range; (5) good physical, chemical and mechanical properties. Nonlinear optical crystal materials can be divided into inorganic materials, organic materials, polymer materials and organometallic complex materials according to their physical and chemical properties. At present, the vast majority of nonlinear optical crystal materials on the market are inorganic materials. According to their different application bands, they can be divided into three categories: ultraviolet band, visible band and infrared band. Among them, nonlinear optical crystal materials in the ultraviolet and visible bands can already meet the requirements of practical applications.

[0003] The nonlinear optical crystal materials in the infrared band are mainly semiconductor materials with ABC2-type chalcopyrite structure, such as AgGaS2, AgGaSe2, ZnGeP2, etc. These compounds have large nonlinear optical coefficients and high mid- and far-infrared transmittance, but they also have serious disadvantages such as low laser damage threshold and two-photon absorption, which limits their application. Therefore, exploring new infrared nonlinear optical crystal materials with application prospects is a difficulty and hot spot in the current research field of nonlinear optical materials. Summary of the invention

[0004] In order to improve the above technical problems, the present invention provides a salt-coated infrared nonlinear optical crystal, a preparation method and use thereof. The optical crystal material has excellent second-order nonlinear optical properties, can achieve phase matching in the infrared band, and its powder frequency doubling intensity can reach 1.0 to 2.0 times that of the commercial material AgGaS2 crystal, and its laser damage threshold is 30 to 40 times that of the AgGaS2 crystal, thereby achieving a good balance between a large second-order frequency doubling coefficient and a high laser damage threshold.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a chemical formula of [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ] compounds.

[0007] The present invention also provides the [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ] compound preparation method, comprising: mixing Ba source, Zn source, Ga source, elemental S and alkali metal halide AX raw materials, and preparing [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ] compounds.

[0008] According to an embodiment of the present invention, the Ba source is at least one of simple Ba, BaO, BaS or BaSO4.

[0009] According to an embodiment of the present invention, the Zn source is single substance Zn or ZnO or ZnS.

[0010] According to an embodiment of the present invention, the Ga source is Ga single substance or GaO or Ga2S3.

[0011] According to an embodiment of the present invention, in the alkali metal halide AX, A is selected from K, Rb or Cs, preferably Cs; X is selected from Cl, Br or I, preferably I.

[0012] According to an embodiment of the present invention, the molar ratio of the Ba source, the Zn source, the Ga source, the elemental S, and the alkali metal halide AX may be 22:14:18:(1-60):(1-15).

[0013] According to an embodiment of the present invention, the insulation temperature of the high temperature solid phase method is 700-1200°C, preferably 900-1100°C, and exemplified by 700°C, 800°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, and 1200°C.

[0014] According to an embodiment of the present invention, the holding time of the high temperature solid phase method is not less than 50 hours, preferably 100 to 200 hours, exemplified by 70 hours, 100 hours, 120 hours, 150 hours, 180 hours, and 200 hours.

[0015] According to an embodiment of the present invention, the high temperature solid phase method specifically comprises: putting the raw material into a sealed container and placing it in a heating device, heating it up, keeping it at high temperature, and cooling it down to room temperature to obtain the [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ] compounds.

[0016] The room temperature in the present invention refers to no higher than 100°C, preferably no higher than 50°C.

[0017] Preferably, the high temperature solid phase method is carried out under vacuum conditions. Further preferably, the sealed container has a vacuum environment, for example, the vacuum pressure is 10 -4 ~10 -3 Pa.

[0018] Preferably, the sealed container is a sealed quartz reaction tube.

[0019] Preferably, the cooling refers to cooling the product prepared by the high temperature solid phase method, preferably cooling to 200-500°C at a rate not exceeding 5°C / hour and then cooling to room temperature; illustratively, cooling to 400°C at a rate not exceeding 3°C / hour and then cooling to room temperature.

[0020] According to an embodiment of the present invention, the preparation method further comprises washing and drying the product obtained by naturally cooling to room temperature to obtain the [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 For example, the mixture is washed with water (eg, deionized water) and dried with ethanol.

[0021] The present invention also provides an optical crystal, the molecular formula of which is [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ].

[0022] According to an embodiment of the present invention, the structure of the optical crystal belongs to the cubic system, and its space group is Its unit cell parameters are α=90°, β=90°, γ=90°.

[0023] Exemplarily, the unit cell parameters of the optical crystal are α=90°, β=90°, γ=90°.

[0024] According to an embodiment of the present invention, the optical crystal has a non-central three-dimensional grid structure composed of a huge [Zn 12 Ga 16 S 58 ] clusters and [(Zn / Ga)S4] tetrahedrons, connected to each other by sharing vertices S; the alkaline earth metal ion Ba 2 + and sulfate ion SO4 2– Dispersed and filled in the gaps of the three-dimensional grid structure as a charge balance.

[0025] According to an embodiment of the present invention, the structure of the optical crystal is as follows Figure 1 shown.

[0026] According to an embodiment of the present invention, the optical crystal has substantially Figure 2 X-ray crystal diffraction pattern shown in a.

[0027] According to an embodiment of the present invention, the optical crystal is an infrared nonlinear optical crystal.

[0028] According to an embodiment of the present invention, the powder frequency-doubled intensity of the optical crystal is 1.0 to 2.0 times, for example, 1.5 times, that of the commercial material AgGaS2 crystal.

[0029] According to an embodiment of the present invention, the laser damage threshold of the optical crystal is 30 to 40 times, for example, 37 times, of that of the commercial material AgGaS2 crystal.

[0030] The present invention also provides a method for preparing the above optical crystal, comprising mixing a Ba source, a Zn source, a Ga source, a single substance S and an alkali metal halide AX raw material, and preparing the optical crystal by a high temperature solid phase method.

[0031] According to an embodiment of the present invention, the Ba source is at least one of simple Ba, BaO, BaS or BaSO4.

[0032] According to an embodiment of the present invention, the Zn source is single substance Zn or ZnO or ZnS.

[0033] According to an embodiment of the present invention, the Ga source is Ga single substance or GaO or Ga2S3.

[0034] According to an embodiment of the present invention, in the alkali metal halide AX, A is selected from K, Rb or Cs, preferably Cs; X is selected from Cl, Br or I, preferably I.

[0035] According to an embodiment of the present invention, the molar ratio of the Ba source, the Zn source, the Ga source, the elemental S, and the alkali metal halide AX may be 22:14:18:(1-60):(1-15).

[0036] According to an embodiment of the present invention, the insulation temperature of the high temperature solid phase method is 700-1200°C, preferably 900-1100°C, and exemplified by 700°C, 800°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, and 1200°C.

[0037] According to an embodiment of the present invention, the holding time of the high temperature solid phase method is not less than 50 hours, preferably 100 to 200 hours, exemplified by 70 hours, 100 hours, 120 hours, 150 hours, 180 hours, and 200 hours.

[0038] According to an embodiment of the present invention, the high temperature solid phase method specifically comprises: putting the raw material into a sealed container and placing it in a heating device, heating it up, keeping it at a high temperature, and cooling it down to room temperature to obtain the optical crystal. The room temperature in the present invention refers to no higher than 100°C, preferably no higher than 50°C.

[0039] Preferably, the high temperature solid phase method is carried out under vacuum conditions. Further preferably, the sealed container has a vacuum environment, for example, the vacuum pressure is 10 -4 ~10 -3 Pa.

[0040] Preferably, the sealed container is a sealed quartz reaction tube.

[0041] Preferably, the heating and temperature raising refers to heating to a holding temperature, and the holding temperature is selected from 700 to 1200°C, preferably 900 to 1100°C. Exemplarily, the temperature may be 1000°C.

[0042] Preferably, the high temperature insulation time is not less than 50 hours, preferably 100 to 200 hours. Exemplarily, the high temperature insulation refers to insulation at 950° C. for 150 hours.

[0043] Preferably, the cooling refers to cooling the product prepared by the high temperature solid phase method, preferably cooling to 200-500°C at a rate not exceeding 5°C / hour and then cooling to room temperature; illustratively, cooling to 400°C at a rate not exceeding 3°C / hour and then cooling to room temperature.

[0044] Preferably, the preparation method further comprises washing and drying the product obtained by naturally cooling to room temperature to obtain the optical crystal, for example, washing with water (such as deionized water) and drying with ethanol.

[0045] The present invention also provides a nonlinear optical crystal material, namely, the [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ]Optical crystal.

[0046] The present invention also provides the above-mentioned [Ba 22 (SO4)5][Zn 14 Ga 18 S 58] The use of compounds and / or optical crystal materials, for example, in infrared detectors, infrared lasers, photorefractive information processing, laser frequency conversion, near-infrared probes, etc.

[0047] The present invention also provides an infrared detector, the infrared detector comprising the above-mentioned [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ] compounds and / or optical crystals.

[0048] The present invention also provides an infrared laser, the infrared laser comprising the above-mentioned [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ] compounds and / or optical crystals.

[0049] Beneficial effects of the present invention:

[0050] The invention provides a salt-coated infrared nonlinear optical crystal material, which has excellent second-order nonlinear optical properties, namely, phase matching can be achieved in the infrared band, has a moderate birefringence, a wide light transmittance range, and a strong double frequency response. The double frequency intensity can reach 1.0 to 2.0 times that of the commercial material AgGaS2, and the laser damage threshold is 30 to 40 times that of the AgGaS2 crystal, thus achieving a good balance between a large second-order double frequency coefficient and a high laser damage threshold.

[0051] This infrared nonlinear optical crystal has important application value in high-tech fields such as laser frequency conversion, near-infrared probes, and photorefractive information processing, especially in infrared detectors and infrared lasers. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 The present invention [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ]Schematic diagram of the crystal structure.

[0053] Figure 2 The present invention [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ]Simulated X-ray diffraction pattern of crystals. DETAILED DESCRIPTION

[0054] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0055] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0056] Example 1

[0057] BaO, BaS, ZnS, Ga2S3 and KI were mixed evenly in a molar ratio of 20:2:14:9:10 to obtain a raw material. The raw material was placed in a quartz crucible, and the crucible containing the raw material was placed in a quartz reaction tube, and vacuum was drawn to 10 -3 Pa and melt the sealed quartz reaction tube with hydrogen-oxygen flame. Place the quartz reaction tube in a tube furnace with a temperature controller, heat it to 950°C, and keep it for 120 hours. Then cool it down to 350°C at a rate of 2°C / hour, and stop heating. Cool it naturally to room temperature, wash the product with deionized water and dry it with ethanol, and the light yellow block crystal obtained is the infrared nonlinear optical crystal material [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ], recorded as sample 1.

[0058] Example 2

[0059] BaSO4, BaS, ZnS, Ga2S3 and CsI were mixed evenly in a molar ratio of 5:17:14:9:5 to obtain a raw material. The raw material was placed in a quartz crucible, and the crucible containing the raw material was placed in a quartz reaction tube, and vacuum was drawn to 10 -3 Pa and melt the sealed quartz reaction tube with hydrogen-oxygen flame. Place the quartz reaction tube in a tube furnace with a temperature controller, heat it to 1000°C, and keep it for 100 hours. Then cool it down to 450°C at a rate of 3°C / hour, and stop heating. Cool it naturally to room temperature, wash the product with deionized water and dry it with ethanol, and the light yellow block crystal obtained is the infrared nonlinear optical crystal material [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ], recorded as sample 2.

[0060] Example 3

[0061] Ba, BaO, BaS, ZnS, Ga, S and RbI were mixed evenly in a molar ratio of 7:5:10:14:18:39:8 to obtain a raw material. The raw materials were placed in a quartz crucible, and the crucible containing the raw materials was placed in a quartz reaction tube, and vacuum was drawn to 10 -3 Pa and melt the sealed quartz reaction tube with hydrogen-oxygen flame. Place the quartz reaction tube in a tube furnace with a temperature controller, heat it to 1050°C, and keep it for 70 hours. Then cool it down to 500°C at a rate of 4°C / hour, and stop heating. Cool it naturally to room temperature, wash the product with deionized water and dry it with ethanol, and the light yellow block crystal obtained is the infrared nonlinear optical crystal material [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ], recorded as sample 3.

[0062] (1) Structural characterization of samples

[0063] The X-ray single crystal diffraction of the sample in Example 1 was carried out on a Mercury 724 single crystal diffractometer with a Mo target and a K α Radiation source (λ = 0.07107nm), test temperature 293K. And the structure was analyzed by Shelx-2014. The crystallographic data of the sample are shown in Table 1, and the crystal structure diagram is shown in Figure 1 shown.

[0064] Table 1 Sample [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ] crystallographic data

[0065]

[0066] The structure of the resulting crystal has a non-central three-dimensional grid structure composed of a huge [Zn 12 Ga 16 S 58 ] clusters and [(Zn / Ga)S4] tetrahedrons, connected to each other by sharing vertices S; the alkaline earth metal ion Ba 2+ and sulfate ion SO4 2– Dispersed and filled in the gaps of the three-dimensional grid structure as a charge balance.

[0067] (2) Characterization of optical properties of samples

[0068] The powder SHG performance and laser damage threshold of the samples are shown in Table 2.

[0069] Table 2 Optical performance data of samples

[0070]

[0071] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A chemical formula of [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ] compounds.

2. Claim 1 [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ] A method for preparing a compound, characterized in that: The preparation method comprises mixing a Ba source, a Zn source, a Ga source, a single substance S and an alkali metal halide AX raw material, and preparing [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ] compounds.

3. The preparation method according to claim 2, characterized in that: The Ba source is at least one of Ba element, BaO, BaS or BaSO4. Preferably, the Zn source is single substance Zn or ZnO or ZnS. Preferably, the Ga source is Ga element or GaO or Ga2S3. Preferably, in the alkali metal halide AX, A is selected from K, Rb or Cs; and X is selected from Cl, Br or I. Preferably, the molar ratio of the Ba source, the Zn source, the Ga source, the elemental S and the alkali metal halide AX may be 22:14:18:(1-60):(1-15). Preferably, the insulation temperature of the high temperature solid phase method is 700-1200° C., preferably 900-1100° C.; the insulation time of the high temperature solid phase method is not less than 50 hours, preferably 100-200 hours.

4. An optical crystal, characterized in that: The molecular formula of the optical crystal is [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ]. Preferably, the structure of the optical crystal belongs to the cubic system, and its space group is Its unit cell parameters are α=90°, β=90°, γ=90°. Preferably, the optical crystal has a non-central three-dimensional grid structure composed of a huge [Zn 12 Ga 16 S 58 ] clusters and [(Zn / Ga)S4] tetrahedrons, connected to each other by sharing vertices S; the alkaline earth metal ion Ba 2+ and sulfate ion SO4 2– Dispersed and filled in the gaps of the three-dimensional grid structure as a charge balance. Preferably, the optical crystal is an infrared nonlinear optical crystal. Preferably, the powder frequency-doubled intensity of the optical crystal is 1.0 to 2.0 times that of the commercial material AgGaS2 crystal. Preferably, the laser damage threshold of the optical crystal is 30 to 40 times that of the commercial material AgGaS2 crystal.

5. The method for preparing an optical crystal according to claim 4, characterized in that: The preparation method comprises mixing a Ba source, a Zn source, a Ga source, a single substance S and an alkali metal halide AX raw material, and preparing the optical crystal by a high-temperature solid phase method. Preferably, the Ba source is at least one of Ba element, BaO, BaS or BaSO4. Preferably, the Zn source is single substance Zn or ZnO or ZnS. Preferably, the Ga source is Ga element or GaO or Ga2S3. Preferably, in the alkali metal halide AX, A is selected from K, Rb or Cs; and X is selected from Cl, Br or I. Preferably, the molar ratio of the Ba source, the Zn source, the Ga source, the elemental S and the alkali metal halide AX may be 22:14:18:(1-60):(1-15).

6. The preparation method according to claim 5, characterized in that: The insulation temperature of the high temperature solid phase method is 700-1200° C., preferably 900-1100° C.; the insulation time of the high temperature solid phase method is not less than 50 hours, preferably 100-200 hours. Preferably, the preparation method further comprises washing and drying the product obtained by naturally cooling to room temperature to obtain the optical crystal.

7. A nonlinear optical crystal material, namely, [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ]Optical crystal.

8. Use of the optical crystal material according to claim 7 in infrared detectors, infrared lasers, photorefractive information processing, laser frequency conversion, near-infrared probes, etc.

9. An infrared detector, characterized in that: The infrared detector contains the [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ] compound and / or the optical crystal described in claim 4 and / or the nonlinear optical crystal material described in claim 7.

10. An infrared laser, characterized in that: The infrared laser contains the [Ba 22 (SO4)5][Zn 14 Ga 18 S 58 ] compound and / or the optical crystal described in claim 4 and / or the nonlinear optical crystal material described in claim 7.

Citation Information

Patent Citations

  • Infrared nonlinear optical crystal and preparation method and application thereof

    CN108441955A

  • Infrared nonlinear optical crystal with diamond-like grid structure as well as preparation method and application of infrared nonlinear optical crystal

    CN115772705A